Perbandingan Penetapan Yang Diberikan Oleh Hakim Dalam Menghadapi Permohonan Pembagian Waris Antara Ahli Waris Dan Pewaris Yang Berbeda Agama - Siswoyo, Adinda Putri; M.T.V.M, Sri Maharani; Sutrisno, Sutrisno (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
The issue of inter-religious inheritance in Indonesia has emerged as a multidimensional challenge, which has multiple interpretations with a plurality of inheritance law systems. The decision of the Semarang Religious Court Judge, as reflected in the differences between judges in giving decisions, namely the comparison of the judge's decision in decision Number 190/Pdt.P/2019/PA Smg and decision Number 890/Pdt. P/ 2021 PA JS, marks an important turning point by emphasizing that divergence in religious beliefs can hinder the inheritance process, as stipulated in the Compilation of Islamic Law (KHI). However, the implementation of obligatory wills, which is recognized in jurisprudence Number 1/ Yur/ Ag/ 2018, offers a legal mechanism to overcome these restrictions, providing space for non-Muslim heirs to participate in the distribution of inheritance assets, although with certain restrictions, illustrating efforts to seek balance between adherence to Islamic doctrine and the principles of legal egalitarianism. The ideal conception regarding the distribution of inheritance assets to heirs of different religions from their heirs, as described in Jurisprudence Number 1/ Yur/ Ag/ 2018, shows significant progress in the practice of Islamic law in Indonesia. It recognizes existing social conditions where religious differences within families and wider society are a reality. The recognition of obligatory wills as a legal tool indicates efforts to adapt Islamic law to dynamic and heterogeneous social needs, offering valuable lessons about the law's ability to adapt and respond to the needs of diverse communities. Furthermore, this affirms the importance of the values of justice and equality before the law, in line with human rights principles which emphasize religious freedom and the right to inheritance as essential components of these rights.